2019
DOI: 10.4314/njp.v45i3.5
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Paediatricians on evidence-based medical practice in Nigeria

Abstract: Background: The increasing need for a uniform standard of medical practice necessitates an examination of the impediments to the use of evidencebased medicine. Objective: To examine the knowledge, perceived barriers to the use of evidence-based medicine and the associated profession-related factors among paediatricians in Nigeria. Methods: A cross-sectional survey of paediatricians in Nigeria was conducted between March and April 2013 by Email. The knowledge about evidence-based medicine and systematic reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In our study, 97.6% of the respondents had used EBM in their clinical practice in the past, which is consistent with previous studies of pediatricians (90.8%) and obstetricians (96.6%) in Nigeria ( 10 , 11 ). However, only 71% of our study respondents reported always/often employing EBM in their clinical practice (classified as self-identified EBM users).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, 97.6% of the respondents had used EBM in their clinical practice in the past, which is consistent with previous studies of pediatricians (90.8%) and obstetricians (96.6%) in Nigeria ( 10 , 11 ). However, only 71% of our study respondents reported always/often employing EBM in their clinical practice (classified as self-identified EBM users).…”
Section: Discussionsupporting
confidence: 91%
“…In the context of Nigeria, the adoption of EBM faces unique challenges ( 10 , 11 , 13 ). For example, there are no national guidelines on EBM in Nigeria comparable to those in the UK, Croatia, or USA.…”
mentioning
confidence: 99%
“…Self‐reported awareness of the EBM terms was generally high as was similarly reported among pediatricians in Nigeria 25 . Fewer respondents however, confirmed a good understanding of the terms.…”
Section: Discussionmentioning
confidence: 68%
“…Self-reported awareness of the EBM terms was generally high as was similarly reported among pediatricians in Nigeria. 25 Fewer respondents however, confirmed a good understanding of the terms. Some of the terms were poorly understood for example, heterogeneity which is an essential concept in determining the applicability of evidence to clinical practice and guideline development.…”
Section: Mechanisms and Results In The Context Of The Literaturementioning
confidence: 97%